THE TECHNOLOGY ACCEPTANCE MODEL (TAM) ON PEPPER FARMERS IN BANGKA, INDONESIA - Novyandra Ilham Bahtera; Evahelda; Eddy Jajang Jaya Atmaja; Iwan Setiawan; Riko Irwanto (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
Nowadays, the use of information technology becomes a new business model in which consumers are more open to demand their needs and take over the decision of the ideal product. However, farmers as the producers of agriculture commodities seem to be reluctant to using information technology in selling their products. The study aims to examine the effect of the perceived usefulness and perceived ease of use of information technology towards the attitude of using information technology in pepper farmers’ marketing practices through the technology acceptance model. The study used face-to-face data collection and a structured questionnaire to obtain the primary data from 100 pepper farmers in Bangka Tengah and Bangka Selatan. The finding of the study shows that perceived usefulness and perceived ease of use affect significantly the attitude of using information technology among the pepper farmers in marketing practices. The results will be useful for the government and NGO to provide tools on how to disseminate the technology to potential users